A novel method for delivering ramped cooling reveals rat behaviours at innocuous and noxious temperatures: a comparative study of human psychophysics and rat behaviour - Dunham, James P.; Hulse, Richard P.; Donaldson, Lucy F. (Elsevier, 2015)
Background